Quality-adjusted price changes on the Hungarian mobile market between 2015-2021 - Zoltán Pápai; Péter Nagy; Aliz McLean (International Telecommunications Society (ITS), 2022)
Mobile technology and services have developed dramatically over the past decades, with mobile operators' competing commercial offers providing a wide menu of service packages with varied quality and quantity characteristics. The prices of these commercial offers do not directly reflect the continuous improvements in service characteristics and functionalities over time: the price changes need to be adjusted for quality. In this paper, we estimate the hedonic changes in residential mobile consumer prices on the Hungarian market by controlling for the changes in the relevant service characteristics and quality, between 2015 and 2021. We also attempt to separate the hedonic price changes from the effect of two specific government interventions that occurred in Hungary, namely the changes in the value added tax (VAT) levied on internet services, in 2017 and 2018. Our results show significant hedonic price changes over the observed period of over 30%, which turns out not to be primarily driven by the VAT policy change, but by real improvements in broadly defined service quality.
Keywords: 330; hedonic regression; mobile prices; mobile telecommunications; Hungary